Forecasting thunderstorms around Delhi and Jodhpur during March and June (MAUSAM, 1989)
Total-Totals Index (TTI) has been used to explore  the possibility of forecasting thunder  storm activity around Delhi and Jodhpur during March and June. Higher values of TTI are associated with more favorable conditions of thunderstorm activity. Prediction of thunderstorm within a limited range of TTI IS uncertain when the chances of occurrence and non-occurrence of thunderstorm are equal.